Particle-toughened interlayers enhance mechanical response of composite laminates. (29th September 2019) - Nguyen, Minh Hoang; Davidson, Paul; Waas, Anthony M.
Abstract: Toughened composite materials, where the toughening agents are micro-particles dispersed within the interlayer resin rich regions, provide enhanced delamination resistance. This delay in delamination promotes intralaminar micro- and macro-cracking, thus providing superior toughness. In this paper, a thorough study of damage accumulation was conducted to identify and quantify failure mechanisms in the ± 45 ∘ laminate axial tensile test. Progression of damage accumulation was captured with digital image correlation techniques, in-situ inspection with high-resolution cameras and interrupted tests at different loading stages. Detailed cross-section microscopy of specimens were used to observe progression of crack formation, density of cracks formed and crack branching at the toughened interfaces.